THE PANCREAS OF NEWBORN RABBITS AS A SOURCE OF PROGENITOR CELLS - L. A. Kirsanova; N. V. Baranova; N. N. Skaletsky; V. A. Zaidenov; G. N. Bubentsova; I. A. Pushkova (Вестник трансплантологии и искусственных органов)
The newborn rabbit pancreas was used as a source of ductal epithelial cells. Our approach includes the cultiva- tion of pancreatic tissue microfragments without preliminary islet and duct isolation. Under ordinary conditions we found the epithelial pancreatic cell monolayer. The cultivated monolayer cells were shown by immunofluo- rescence to express special ductal cytokeratin 19 and were insulin- and glucagon-negative for 7–15 days.